A systematic review of problematic gaming: Escapist strategy to cope with difficult life situations - Snigdha Sinha; Manoj Kumar Sharma; Gitanjali Narayanan; Himani Kashyap; AU Shreedevi; Ashwini Tadpatrikar (Industrial Psychiatry Journal)
Gaming as an increasingly common phenomenon and is frequently used as a coping mechanism during difficult life situations, such as grief and bereavement. This coping usually takes place as an avoidant, escapist strategy, which can lead to problematic or excessive gaming, with harmful outcomes. The aim of this study was to review and collate findings from literature on gaming use as an escapist coping strategy during difficult life situations. A systematic review was carried out with the use of the databases such as PubMed, Google Scholar, Research Gate, and APA PsycNet, where English language studies published in peer-reviewed journals were perused. The full text of the studies selected were then reviewed and suitability for the present study was checked with the eligibility criteria. Out of the 35 texts fully reviewed, 18 studies were finalised that fit the eligibility criteria, and out of these, three themes were derived – “Problematic online gaming and difficult life situations”, “Problematic online gaming, coping and escapism ”, and “Types of gaming”, which demonstrated the psychosocial perspective on gaming used as a coping mechanism for difficult situations. This association is further affected by the type of gaming, whether Massive Multi-player Online Role Playing Games (MMORPG) or otherwise. The aetiology (life situations as a causative factor) and manifestation (gaming used for coping), along with the type of gaming were significantly affected by personal and social factors. The study showed findings that support the view of gaming as an escapist coping strategy in difficult life situations. It is therefore important to look into provisions for better social support and individuals’ psychosocial environment while evolving interventions that enhance coping among gamers.